Solar wind with Hydrogen Ion charge Exchange and Large-Scale Dynamics (SHIELD) DRIVE Science Center - Opher, Merav; Richardson, John; Zank, Gary; Florinski, Vladimir; Giacalone, Joe; Sokół, Justyna M.; Toth, Gabor; Buxner, Sanlyn; Kornbleuth, Marc; Gkioulidou, Matina; Nikoukar, Romina; Van der Holst, Bart; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Most stars generate winds and move through the interstellar medium that surrounds them. This movement creates a cocoon formed by the deflection of these winds that envelops and protects the stars. We call these “cocoons” astrospheres. The Sun has its own cocoon, the heliosphere. The heliosphere is an immense shield that protects the Solar System from harsh, galactic radiation. The radiation that enters the heliosphere affects life on Earth as well as human space exploration. Galactic cosmic rays are the dominant source of radiation and principal hazard affecting space missions within our Solar System. Current global heliosphere models do not successfully predict the radiation environment at all locations or under different solar conditions. To understand the heliosphere’s shielding properties, we need to understand its structure and large-scale dynamics. A fortunate confluence of missions has provided the scientific community with a treasury of heliospheric data. However, fundamental features remain unknown. The vision of the Solar wind with Hydrogen Ion charge Exchange and Large-Scale Dynamics (SHIELD) DRIVE Science Center is to understand the nature and structure of the heliosphere. Through four integrated research thrusts leading to the global model, SHIELD will: 1) determine the global nature of the heliosphere; 2) determine how pickup ions evolve from “cradle to grave” and affect heliospheric processes; 3) establish how the heliosphere interacts with and influences the Local Interstellar Medium (LISM); and 4) establish how cosmic rays are filtered by and transported through the heliosphere. The key deliverable is a comprehensive, self-consistent, global model of the heliosphere that explains data from all relevant in situ and remote observations and predicts the radiation environment. SHIELD will develop a “digital twin” of the heliosphere capable of: (a) predicting how changing solar and LISM conditions affect life on Earth, (b) understanding the radiation environment to support long-duration space travel, and (c) contributing toward finding life elsewhere in the Galaxy. SHIELD also will train the next-generation of heliophysicists, a diverse community fluent in team science and skilled working in highly transdisciplinary collaborative environments.